Experiências de (re)início da docência na educação básica: a profissionalidade em foco - Cerminaro-Derisso, Maria Cecília (Universidade Federal de São Carlos, 2020)
The objective of this research was to analyze how the professionalism of the teacher with more than five years of teaching practice in the early years of elementary school is shaped when he/she becomes a beginning teacher in another stage of education - early childhood education - trying to identify the aspects of previous experience that are maintained and those that are (re)built. We start from the hypothesis that the teacher who has experience in one stage of education and starts in a new stage - feeling himself/herself again and, to a certain extent, a beginning teacher - develops his/her actions based on a set of learning experiences that are consolidated by means of experience and that are kept and move between the stages of education and, at the same time, (re)builds a new professionality in a core that is remade, that is, of learning that is characterized according to the specificity of the stage in which he/she works. In this way, the research question was the following: Which aspects of the teaching professionalism are maintained and which are remade when the teacher starts working in a new stage of basic education? Being of a quanti-qualitative nature, the research was developed in a municipal teaching network in the countryside of the state of São Paulo, using a questionnaire and a semi-structured interview as instruments to obtain the data. The first sought to identify the degree of agreement of these professionals in relation to various aspects that are characteristic of the beginning of teaching, as revealed by the literature in the area. The data analysis of the questionnaires served as a basis for the definition of the participants and the elaboration of the instrument for the second stage of the research, the semi-structured interview, in order to deepen the understanding about the construction and reconstruction of the professionalism of female teachers at the beginning of their teaching career. The data, confirming our initial hypothesis, indicate that the participants experienced learning in their first teaching experience that contributed significantly to the quality of the experiences in the new stage with regard to relational and disciplinary knowledge. On the other hand, in relation to what is remade, we find the pedagogical knowledge that constitutes the central point of (re)construction of the teaching professionalism at the beginning of the teaching career, since it holds characteristics, knowledge, skills and competencies specific to the stage of performance, being directly influenced by the context. The study ratifies the need for greater attention and to create more appropriate ways of "initiating" teaching - considering the particularity of this career stage - and extends this understanding - from the consideration of the teaching profession in its specificities - taking into account that the beginning of teaching cannot be considered as a single moment in the profession, and in a defense of the "beginnings" - in the plural - of teaching, since the time of teaching experience does not guarantee, by itself, the knowledge and specific know-how to the different levels, stages and types of teaching, since at each new beginning, the teacher is faced with the need of (re)building his/her professionalism, in a movement in which he/she experiences the insecurities, concerns, and intensive learning characteristic of the beginning teacher.
Experiences of re(starting) of teaching in basic education: profissionalism in focus
Keywords: Inícios da docência; Profissionalidade docente; Experiência; Beginnings of teaching; Teaching professionalism; Experience; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO